Implementation of Storytelling Method Using Hand Puppets to Improve Language Skills in Preschool Children at Aisiyah Bustanul Kindergarten Pekanbaru (JONAH : Journal of Nursing and Homecare, 2026)
When a child reaches an early age, a child needs useful education to complete his future. One of the educations that can be given to children is by developing their language. As a result of delays in child development, especially in the language sector, children will experience obstacles in effective communication. The purpose of this case study scientific paper is to describe the level of language skills in children with the method of implementing storytelling using hand puppets to improve language skills in preschool children at Aisiyah Bustanul Kindergarten Pekanbaru. The type of research used is descriptive using a case study approach with a total of 2 subjects, conducted within 15 minutes for 6 days. In this case study before the implementation of storytelling using hand puppets showed that there was a delay in language development in both research subjects. After the implementation of the storytelling method using hand puppets, both subjects experienced an increase as evidenced by the increase in aspects of language development from starting to develop to developing very well and failing to pass on the DDST sheet. It is concluded that the implementation of the storytelling method using hand puppets can improve language development in preschool children.